(3x-6)(2x-9)=

Simple and best practice solution for (3x-6)(2x-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-6)(2x-9)= equation:


Simplifying
(3x + -6)(2x + -9) = 0

Reorder the terms:
(-6 + 3x)(2x + -9) = 0

Reorder the terms:
(-6 + 3x)(-9 + 2x) = 0

Multiply (-6 + 3x) * (-9 + 2x)
(-6(-9 + 2x) + 3x * (-9 + 2x)) = 0
((-9 * -6 + 2x * -6) + 3x * (-9 + 2x)) = 0
((54 + -12x) + 3x * (-9 + 2x)) = 0
(54 + -12x + (-9 * 3x + 2x * 3x)) = 0
(54 + -12x + (-27x + 6x2)) = 0

Combine like terms: -12x + -27x = -39x
(54 + -39x + 6x2) = 0

Solving
54 + -39x + 6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(18 + -13x + 2x2) = 0

Factor a trinomial.
3((2 + -1x)(9 + -2x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Subproblem 2

Set the factor '(9 + -2x)' equal to zero and attempt to solve: Simplifying 9 + -2x = 0 Solving 9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = 0 + -9 -2x = 0 + -9 Combine like terms: 0 + -9 = -9 -2x = -9 Divide each side by '-2'. x = 4.5 Simplifying x = 4.5

Solution

x = {2, 4.5}

See similar equations:

| -3+4(x-1)=13x+6-9x | | 7x-3=4x^2-1 | | 5n^2+20n-30=10 | | 2h+6=h+27 | | .425-.42415= | | 13p+5=-3+9p | | 4=2(m-6) | | 2(x+1)+3(2x+3)=0 | | 4a+3s=380 | | 8(z+1)+5(2z+2)= | | -6+4a=-12+6a | | (2x+8)(3x+5)= | | 0.5(x+60)+1.3x=111 | | (-1)(-5)(-6)= | | (f)-2=9x^2-5x+2 | | -4(3n+2)-6(5-n)=-32 | | 3x=17x | | 3(2k-1)=-38 | | x^2-20x+24=0 | | 3(4z-1)-4(z+3)=3(z+1) | | 6-2(x+2)=x-18 | | 6=5z+2 | | -3y-18=-12 | | sprt(4x^2)=0 | | 3(4z-1)4(z+3)=3(z+1) | | 6(1+5x)-x=-100 | | 9x+90=6x+120 | | 3x-x*lnx=0 | | Y+2=74 | | 4+3(x-3)=9-7(x-2) | | 14-x=17-8 | | X=1436.31-(0.09*X) |

Equations solver categories